Evolution in biosynthetic pathways: two enzymes catalyzing consecutive steps in methionine biosynthesis originate from a common ancestor and possess a similar regulatory region. - Belfaiza, J (1986)
The metC gene of Escherichia coli K-12 was cloned and the nucleotide sequence of the metC gene and its flanking regions was determined. The translation initiation codon was identified by sequencing the NH2-terminal part of beta-cystathionase, the MetC gene product. The metC gene (1185 nucleotides) encodes a protein having 395 amino acid residues. The 5' noncoding region was found to contain a "Met box" homologous to sequences suggestive of operator structures upstream from other methionine genes that are controlled by the product of the pleiotropic regulatory metJ gene. The deduced amino acid sequence of beta-cystathionase showed extensive homology with that of the MetB protein (cystathionine gamma-synthase) that catalyzes the preceding step in methionine biosynthesis. The homology strongly suggests that the structural genes for the MetB and MetC proteins evolved from a common ancestral gene.